Sign language conversion and training by machine learning with an IOT approach - Nazib, Rezoan Ahmed; Ahmed, Tanvir; Siddique, Niloy; Tusher, Jahid Hasan (BRAC Univeristy, 2018)
Cataloged from PDF version of thesis report.